Հայազգի «հրեշավոր երկվորյակները» Մոսուլում. արաբական աղբյուրների վկայությունները - Դանիելյան, Գագիկ (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The reign of Ašot III (953-978) of Bagratid Armenia was marked by peace, political stability and economic prosperity. The king was renowned for his pious and benevolent attitude towards the poor and the disabled. For his charitable deeds, he earned the nickname “merciful” and after his death was even canonized by the Armenian Church. Ibn al-Ǧawzī’s Al-Muntazam fī tārīh al-mulūk wa-l-umam contains an interesting report of two conjoined men, sent in 352 A.H./963 A.D by the “lord of Armenia”, who most probably was Ašot III, to Nāsir al-Dawla al-Hamdānī, the governor of Mosul and al- Ğazīra. It comes clear from the further description that the historian is talking about conjoined twins. Given the high level of the medieval Arabic medicine, the Armenian authorities sent the twins to Mosul, probably hoping that it would be possible to separate them. Other accounts of conjoined twins can be found in the medieval Arabic historiography.
Keywords: Աղբյուրագիտություն; Արաբագիտություն; Պատմություն